Knowledge politics, vulnerability and recognition-based justice: Public participation in renewable energy transitions in India. (January 2021) - Pandey, Poonam; Sharma, Aviram
Abstract: Public participation plays a crucial role in achieving Renewable Energy Transitions (RET). Existing research on energy transitions suggests that for seeking the active participation of all stakeholders, transition frameworks must be sensitive to the dynamic and complex interplay of power and agency. Knowledge politics that determine terms of engagement within energy transition projects often enable asymmetric agency resulting in vulnerability, exclusion and injustices. However, very little is known about how vulnerable and marginal groups resist subversion and re-define terms of engagement. This paper presents three cases of RET projects from India to engage with the interplay of knowledge politics, vulnerability and recognition-based energy justice. The cases bring comparable insights from RET projects on three different energy sources (second-generation bioethanol, advanced biogas and solar micro-grid), initiated by the government, industry and non-governmental actors in India. Based on the qualitative, empirical data gathered through semi-structured interviews, focus group discussions, and ethnographic field observations, we argue that non-participation is a mode of resistance against subversive knowledge politics. Despite projected benefits and "apparent needs", people do not accept the pre-defined roles and identities prescribed for them in RET projects. In contrast, vulnerable and marginal social groups mobilize their agency by framing needs and priorities in relation to situated as well as emergent social, political and ecological identities and demand for recognition-based energy justice.